2018
DOI: 10.1101/324996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pristionchusnematodes occur frequently in diverse rotting vegetal substrates and are not exclusively necromenic, whilePanagrellus redivivoidesis found specifically in rotting fruits

Abstract: The lifestyle and feeding habits of nematodes are highly diverse. Several species of Pristionchus (Nematoda: Diplogastridae), including Pristionchus pacificus, have been reported to be necromenic, i.e. to associate with beetles in their dauer diapause stage and wait until the death of their host to resume development and feed on microbes in the decomposing beetle corpse. We review the literature and suggest that the association of Pristionchus to beetles may be phoretic and not necessarily necromenic. The view… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In laboratory conditions, the females do not lay embryonated eggs (however, we cannot rule out that they lay embryos in some environment). Instead, L1 larvae exit their mother's body through the vulva, as, for example, in the genus Panagrellus in family Panagrolaimidae (Andrássy ; Félix et al ). In the closely related species C. virilis , females lay late‐stage embryonated eggs compared to most Caenorhabditis species (which accumulate few embryos in their uteri) but are not viviparous in standard laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory conditions, the females do not lay embryonated eggs (however, we cannot rule out that they lay embryos in some environment). Instead, L1 larvae exit their mother's body through the vulva, as, for example, in the genus Panagrellus in family Panagrolaimidae (Andrássy ; Félix et al ). In the closely related species C. virilis , females lay late‐stage embryonated eggs compared to most Caenorhabditis species (which accumulate few embryos in their uteri) but are not viviparous in standard laboratory conditions.…”
Section: Resultsmentioning
confidence: 99%
“…C. elegans is known to be found in decaying organic matter such as stems or fruits (Schulenburg and Félix, 2017). A study surveying the environments where Caenorhabditis are commonly found also discovered P. pacificus in samples of rotting stems and fruits (Félix et al, 2018). P. pacificus, like C. elegans, is a bacterivorous hermaphrodite.…”
Section: Predators and Fear Conditioningmentioning
confidence: 99%